경영시스템 도입 중소기업의 품질이행율 향상을 위한 품질기록 관리운영의 표준화 사례연구 - 조철희; Cho Chul-hee; 박병화; Park Byeong Hwa; 박진이; Park Jini (品質經營學會誌, 2019)
Purpose: In an infinite market competition, companies are adopting management systems to gain a competitive advantage. The expectancy effect of the management system is management performance improvement and accurate measurements. These can be made through quality records with integrity and maintainability. This paper examines the operation of records management standards, which are records, storage and management standards for quality records to understand the needs of records management standards and empathize with their needs. Methods: This paper examines PEC’s (Pields Engineering Co., Ltd.) specific processes and standards for integrating individual management systems and establishing records management standards. We also look at the specific features of the Search Tool and Document Storage Management Standards that support records management standards. Results: The integration process of PEC's individual management system consists of five steps. A PDCA-based process was established to erode the confusion and inefficiencies caused by overlap between individual management systems. Also, by accurately grasping corporate competence, PEC established a record management standard suitable for the characteristics of the company. PEC's records management standards are used as a useful standard for organizing quality records, and have an impact on management performance improvement. Conclusion: PEC's records management standards enable the verification of quality performance rates and performance measures. Companies can implement appropriate quality improvement strategies based on the numbers identified by introducing records management standards. Companies can succeed in improving management performance when operating quality management that combines performance measurement techniques and records management standards.